2017
DOI: 10.1002/2017ja024364
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect electron precipitation effect on nitric oxide in the polar middle atmosphere, using a full‐range energy spectrum

Abstract: In April 2010, a coronal mass ejection and a corotating interaction region on the Sun resulted in an energetic electron precipitation event in the Earth's atmosphere. We investigate direct and indirect nitric oxide (NO) response to the electron precipitation. By combining electron fluxes from the Total Energy Detector and the Medium Energy Proton and Electron Detector on the National Oceanic and Atmospheric Administration's Polar‐orbiting Operational Environmental Satellites, we obtain a continuous energy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…The geomagnetic storm period of April 2010 was driven by a combination of both co-rotating interaction regions associated with high-speed solar wind streams and of coronal mass ejections associated with dense transient solar wind flows. This period is also described in more detail in Smith-Johnsen et al (2017). We use the Disturbance Storm Time (Dst) index to characterize the storm onset and evolution.…”
Section: The Waccm-d Simulations and Ancillary Datamentioning
confidence: 99%
“…The geomagnetic storm period of April 2010 was driven by a combination of both co-rotating interaction regions associated with high-speed solar wind streams and of coronal mass ejections associated with dense transient solar wind flows. This period is also described in more detail in Smith-Johnsen et al (2017). We use the Disturbance Storm Time (Dst) index to characterize the storm onset and evolution.…”
Section: The Waccm-d Simulations and Ancillary Datamentioning
confidence: 99%
“…In the mesosphere‐lower‐thermosphere (MLT), descent or mixing in the vortex (Fisher et al, ) is required to transport nitrogen oxides (NO x = NO + NO 2 ) produced by energetic particle precipitation (EPP) from the thermosphere to the stratosphere (Meraner & Schmidt, ; Randall et al, , and references therein). This process, known as the EPP Indirect Effect (EPP IE, Randall et al, ), has been extensively observed (e.g., Bailey et al, ; Callis et al, ; Hendrickx et al, ; Natarajan et al, ; Randall et al, , , ; Rinsland et al, ; Russell et al, ; Siskind et al, , ; Smith‐Johnsen et al, , and references therein). The polar vortex plays a key role in this process in that it confines the EPP‐NO x to high latitudes in polar night conditions where the chemical lifetime is long and descent to the stratosphere is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Still, with few exceptions, the MEPED 0°detector is used as quantitative measurement of the MEE precipitation (e.g., Arsenovic et al, 2016;Codrescu & Fuller-Rowell, 1997;Smith-Johnsen et al, 2017). These studies provide a useful first approximation for the minimum impact of MEE upon the atmosphere.…”
Section: Introductionmentioning
confidence: 99%